FACTORS INFLUENCING PREGNANT WOMEN'S CONFIDENCE IN THE USE OF DELIVERY FACILITIES IN LALAFANG POLINDES, PANTAR TIMUR ALOR DISTRICT - Inayah Vauzi Kasim (Master of Public Health Program Universitas STRADA Indonesia, 2022)
Childbirth in a health service facility is one of the key elements in reducing maternal and newborn mortality rates, besides that the choice of birth assistance is one of the factors that determines the implementation of a safe and healthy delivery process. The aim of this research is to determine the factors that influence pregnant women's confidence in using delivery facilities at the Lalafang Polindes, Pantar Timur Alor District This research design uses descriptive qualitative using a case study approach. The sampling method uses techniques Purposive Sampling. The informants in this research were pregnant women in the third trimester at the Lalafang Polindes, Pantar Timur Alor District on May – June 2022. The instruments used were structured interviews or in-depth interviews. The results of the research show that informants have confidence in using birthing facilities, namely giving birth in health facilities (polindes) and there are still informants who have confidence in using birthing facilities, namely giving birth in non-health facilities. Informants have confidence in using birth facilities, namely giving birth assisted by health workers, and there are still informants who have confidence in using birth facilities, namely giving birth assisted by a traditional birth attendants (dukun). It was concluded that pregnant women's beliefs influence the use of birth facilities, which includes trust in the place of birth and birth attendants.